The Impact of Attributing Causes to Legal Rulings in the Ḥanafī School: An Applied Uṣūlī Study - Al-Dlain, Husni (Jordan Journal of Islamic Studies, 2025)
The study aimed to investigate the effect of adding ‘ʿillat (legal reasons), causes, or conditions to rulings and the extent of their influence in usage among the Usul scholars in directing the ruling and clarifying the meaning in the branches of the Hanafi school. The study followed the descriptive method by describing the original basis, the analytical method by categorizing the issues, and the deductive method by examining the original basis of the ruling. The study concluded that the effect on the ruling differs depending on whether it is added to a complete and true ʿillah, as opposed to a ruling added to an incomplete ʿillah or to a ‘cause of the ‘illah. It also clarified the impact of linking the ruling to the ‘illah in the branches according to the Hanafis. The study emphasized the importance of studying the rules of adding ‘illat due to their effect on directing rulings.